Biography of an Artifact: The Theratron Junior and Canada’s Atomic Age - Pantalony, David (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2011)
In this article I examine the life of an artifact, the Theratron Junior, a sleek green radiotherapy machine from 1956 displayed in a permanent exhibit at the Canada Science and Technology Museum. It is currently seen through the lens of Canadian innovations, but the Theratron Junior brims with features and history that touch on several other historical narratives—scientific, commercial, labour, aesthetics and patient experience. The striking “sea foam” green paint, for example, has inspired an independent exhibition at the museum on the colour green in twentieth-century medicine. In addition, research into the former life of the specific machine on display (serial no. 15 from 1956), including the people who made and used it, has produced a reinvigorated artifact biography that enriches and challenges conventional narratives from Canada’s early atomic era. The lessons from careful artifact studies are readily clear—we are missing opportunities by taking for granted the most familiar items on our museum floors.